Rubrik. Issue 5 (July 2015) - Britzen, S.; Eckart, A.; Lämmerzahl, C.; Roland, J.; Brockamp, M.; Hackmann, E.; Kunz, J.; Macias, A.; Malchow, R.; Sabha, N.; Shahzamanian, B.
Abstract Detailed and long‐term VLBI (Very Long Baseline Interferometry) studies of the variable jets of supermassive black holes helps us to understand the emission processes of these fascinating phenomena. When observed and traced precisely, jet component kinematics reveals details about the potential motion of the jet base. Following this motion over decades with VLBI monitoring reveals – in some cases – the signatures of precession. While several processes can cause precession, the most likely cause seems to be a supermassive binary black hole in the central region of the AGN. We present examples of the analysis of high‐resolution VLBI observations which provides us with insight into the physics of these objects and reveals evidence for the presence of double black hole cores. EHT (Event Horizon Telescope) observations will probably soon tell us more about the jet origin and launching mechanism at the very centers of nearby active galactic nuclei. An important question to be addressed by the EHT and related observations will be whether Sgr A*, the supermassive black hole in the Galactic Center, has a jet as well. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)